Optimal level of added salt to minimize the risk of associated chemical hazards of small-sized anchovy (Stolephorus indicus) stored at ambient and refrigerated temperatures - Tiamsai, Rojyotin; Waiprib, Yaowapha; Runglerdkriangkrai, Jiraporn; Somjit, Kingduean (Agriculture and Natural Resources, 2022)
Importance of the work: Practical protocol for post-harvest handling of small-sized (less than 12 cm) anchovy by means of chilling and salting is needed to minimize the risk of associated chemical hazards. Objectives: The objective of this study was to establish the optimal level of added salt for anchovy (Stolephorus indicus) stored at different temperatures. Materials & Methods: Changes in water phase salt (WPS) and quality of anchovy (7.99 ± 0.38 cm in length) salted at 2%, 4%, 6%, 8%, 10% and 12% w/w, were monitored during 5 hr post salting at ambient temperature (33 ± 3°C) and refrigerated temperature (4 ± 1°C). Results: WPS levels of 10% or higher were achieved when the level of added salt was 8–12% w/w, while water activity values of 0.94 or lower were achieved when the level of added salt was 6–12% w/w for anchovy stored at both temperatures (p < 0.05). The time ranges practically required to reach 10% WPS during refrigerated storage of anchovy salted at 8–10% w/w and 12% w/w were 4 hr and 2 hr, respectively. After 5 hr of storage, salting anchovy at 8–12% w/w either stored at ambient or chilled temperature resulted in a histamine content below 2 mg/100 g and total volatile base nitrogen and trimethylamine contents below the limits of acceptability for human consumption. Main finding: It could be concluded that the combination of a prescribed salt level of 8–12% w/w and refrigerated storage of anchovy being used as a raw material provided a high level of assurance that the microbial growth and chemical changes could be retarded.